Male Sexual Dysfunction - Danyon Anderson; John Laforge; Maggie M. Ross; Robert Vanlangendonck; Jamal Hasoon; Omar Viswanath; Alan D. Kaye; Ivan Urits (Health Psychology Research)
Male sexual dysfunction is a series of conditions, most notably including erectile dysfunction (ED), Peyronie's disease (PD), and premature ejaculation (PE), defined by impaired sexual functioning. The prevalence of male sexual dysfunction increases with age and is relatively high with greater than 50% of men aged 40 to 70 describing some degree of erectile dysfunction. Risk factors for male sexual dysfunction include age, diabetes mellitus (DM), cancer, stroke, hypertension, penile trauma, depression, anxiety, and disturbance in central serotonin neurotransmission and 5-HT postsynaptic receptor functioning. Sexual questionnaires including the International Index of Erectile Dysfunction, Sexual Health Inventory for Men, and the Premature Ejaculation Diagnostic Tool are useful in screening for these disorders. Focused history and physical can establish diagnoses. For a condition to be diagnosed as male sexual dysfunction, the patient or their partner must view their sexual functioning as impaired. Treatment of male sexual dysfunction is etiology dependent. For ED, first-line therapy is a phosphodiesterase-5 inhibitor or mental health care for psychogenic ED. More complicated cases may be treated with injections, surgery, or shockwave therapy. PD is either treated with medications for pain management, collagenase clostridium histolyticum injection, corpoplasty, plication, or shockwave therapy. PE may be treated behaviorally or with SSRIs as first line medication.